2019
DOI: 10.1186/s13287-019-1167-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PTGS1 promotes osteogenic differentiation of adipose-derived stem cells by suppressing NF-kB signaling

Abstract: Background Tissue inflammation is an important problem in the field of human adipose-derived stem cell (ASC)-based therapeutic bone regeneration. Many studies indicate that inflammatory cytokines are disadvantageous for osteogenic differentiation and bone formation. Therefore, overcoming inflammation would be greatly beneficial in promoting ASC-mediated bone regeneration. The present study aims to investigate the potential anti-inflammatory role of Prostaglandin G/H synthase 1 (PTGS1) during the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Our transcriptomic analysis identified RNA1.2 as downregulating PIM1 (Nihira et al, 2010 ) and upregulate SEMA3A (Sumi et al, 2018 ), which have been reported to activate and suppress, respectively, NF-κB signaling in other cell types and contexts, and thus may contribute to RNA1.2 stimulated increase in IL-6 levels. However, the screen also identified RNA1.2 as downregulating six other potential inhibitors of NF-κB: RCAN1 (Chen et al, 2017 ), IFRD1(Micheli et al, 2011 ), HBEGF (Mehta and Besner, 2005 ), SDC1 (Zhang et al, 2016 ), TSC22D3 (Di Marco et al, 2007 ) and PTGS1 (Wang et al, 2019 ). Their modulation of NF-κB is likely to be contextual to cell type and biological process, and thus further work will be required to determine whether they influence NF-κB activity during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our transcriptomic analysis identified RNA1.2 as downregulating PIM1 (Nihira et al, 2010 ) and upregulate SEMA3A (Sumi et al, 2018 ), which have been reported to activate and suppress, respectively, NF-κB signaling in other cell types and contexts, and thus may contribute to RNA1.2 stimulated increase in IL-6 levels. However, the screen also identified RNA1.2 as downregulating six other potential inhibitors of NF-κB: RCAN1 (Chen et al, 2017 ), IFRD1(Micheli et al, 2011 ), HBEGF (Mehta and Besner, 2005 ), SDC1 (Zhang et al, 2016 ), TSC22D3 (Di Marco et al, 2007 ) and PTGS1 (Wang et al, 2019 ). Their modulation of NF-κB is likely to be contextual to cell type and biological process, and thus further work will be required to determine whether they influence NF-κB activity during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the precise molecular mechanisms of osteogenesis is of immense importance for promoting the osteogenic efficacy and clinical application of stem cells in bone regeneration. To date, most research has focused on the study of epigenetic and transcriptional factors involving stem cells themselves [4547], whereas few studies have focused on the effects of exosome “cargo” on the osteogenic differentiation of stem cells. It has been noted that exosomes can regulate corresponding biological processes by affecting related pathways in receptor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al showed that in ADT-treated PCa, ZBTB46 levels were enhanced by loss of the expression of the SAM pointed domain-containing ETS transcriptional factor ( SPDEF ), which is believed to act as a tumor suppressor gene and to be regulated by AR signaling [118]. A low level of SPDEF leads to an increase in the expression of ZBTB46 , thus facilitating an abundance of prostaglandin endoperoxide synthase 1 ( PTGS1 ), which was reported to participate in inflammation, arthritis, and cancer pathophysiology [119,120,121,122]. Those studies demonstrated that ZBTB46 acts as a transcriptional coactivator and induces PTGS1 expression.…”
Section: Zinc Finger and Btb Domain-containing Protein 46 (Zbtb46)mentioning
confidence: 99%